Y = 2x - 5
3x + 8y + 32 = 56
3x + 8(2x - 5) + 32 = 56
3x + 8(2x) - 8(5) + 32 = 56
3x + 16x - 40 + 32 = 56
19x - 8 = 56
<u> + 8 + 8</u>
<u>19x</u> = <u>64</u>
19 19
x = 3.4
y = 2(3.4) - 5
y = 6.8 - 5
y = 1.8
(x, y) = (3.4, 1.8)
You solve an equation like this by adding the opposite of the constant to both sides of the equation.
... V -16 +16 = -32 +16 . . . . . addition property of equality: if a=c, then a+b = c+b
... V + 0 = -16 . . . . . . . . . . . . additive inverse property of integers: -16+16 = 0
... V = -16 . . . . . . . . . . . . . . . identity element of addition: V+0 = V
_____
<em>You can always do the same thing to both sides of an equation.</em> Here, it is useful to add the opposite of -16 to both sides. That way the constant on the left becomes zero, so you only have the variable by itself—which is what you want.
You need to multiply the amount by the tax
Answer:
Step-by-step explanation:
and also you are diviing the numbers then subtracting 9